Antarctic climate and ice-sheet configuration during the early Pliocene interglacial at 4.23 Ma - Golledge, Nicholas R.; Thomas, Zoë A.; Levy, Richard H.; Gasson, Edward G. W.; Naish, Timothy R.; McKay, Robert M.; Kowalewski, Douglas E.; Fogwill, Christopher J. (Climate of the past, 2017)
The geometry of Antarctic ice sheets during warm periods of the geological past is difficult to determine from geological evidence, but is important to know because such reconstructions enable a more complete understanding of how the ice-sheet system responds to changes in climate. Here we investigate how Antarctica evolved under orbital and greenhouse gas conditions representative of an interglacial in the early Pliocene at 4.23 Ma, when Southern Hemisphere insolation reached a maximum. Using offline-coupled climate and ice-sheet models, together with a new synthesis of high-latitude palaeoenvironmental proxy data to define a likely climate envelope, we simulate a range of ice-sheet geometries and calculate their likely contribution to sea level. In addition, we use these simulations to investigate the processes by which the West and East Antarctic ice sheets respond to environmental forcings and the timescales over which these behaviours manifest. We conclude that the Antarctic ice sheet contributed 8.6 ± 2.8 m to global sea level at this time, under an atmospheric CO2 concentration identical to present (400 ppm). Warmer-than-present ocean temperatures led to the collapse of West Antarctica over centuries, whereas higher air temperatures initiated surface melting in parts of East Antarctica that over one to two millennia led to lowering of the ice-sheet surface, flotation of grounded margins in some areas, and retreat of the ice sheet into the Wilkes Subglacial Basin. The results show that regional variations in climate, ice-sheet geometry, and topography produce long-term sea-level contributions that are non-linear with respect to the applied forcings, and which under certain conditions exhibit threshold behaviour associated with behavioural tipping points.